2020
DOI: 10.3390/pharmaceutics12121239
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Veterinary Dosage Forms—A Comparative Study of Three Semi-Solid Extrusion 3D Printers

Abstract: Currently, the number of approved veterinary medicines are limited, and human medications are used off-label. These approved human medications are of too high potencies for a cat or a small dog breed. Therefore, there is a dire demand for smaller doses of veterinary medicines. This study aims to investigate the use of three semi-solid extrusion 3D printers in a pharmacy or animal clinic setting for the extemporaneous manufacturing of prednisolone containing orodispersible films for veterinary use. Orodispersib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In vitro dissolution studies for all of the fabricated dosage forms followed non-Fickian diffusion mechanism. The results of this studies indicated the potential of SSE technique of 3D objects manufacturing of LADDS specifically for veterinary purposes [161].…”
Section: Sjöholm Et Al Have Compared the Function Of Three Different ...mentioning
confidence: 65%
“…In vitro dissolution studies for all of the fabricated dosage forms followed non-Fickian diffusion mechanism. The results of this studies indicated the potential of SSE technique of 3D objects manufacturing of LADDS specifically for veterinary purposes [161].…”
Section: Sjöholm Et Al Have Compared the Function Of Three Different ...mentioning
confidence: 65%
“…Since the number of approved veterinary drugs is limited, it is common to use off-label human medicines. The manufacture of prednisolone loaded ODFs for veterinary use in an animal clinical setting has set a precedent for dose personalisation for animals (114).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Promising results are obtained regarding 3D printing products that are biocompatible and that can be used in tissue or organ replacement, and studies are continuing intensively (Jamieson et al, 2021). There are also studies on the production of pharmaceutical products to be used in veterinary medicine with 3D printing (Martin et al, 2020;Sjöholm et al, 2020). The first study on the clinical use of 3D printing products with 3D image reconstruction in veterinary medicine was published by Harrysson et al (2003).…”
Section: D Printing In Veterinary Medicinementioning
confidence: 99%